Literacy Culture Strengthening Programs to Stimulate Reading Interest for Children at Early Age - Mila Faila Shofa; M Heri Yuli Setyawan (Department of Early childhood Education, 2018)
This research aims are to describe the concept of literacy culture on children at early age and to describe the implementation of literacy culture strengthening program on children at early age enrolled at PAUD Inklusi Saymara. The research method used is descriptive qualitative, and the research is conducted at PAUD Inklusi Saymara Kartasura, Sukoharjo, Jawa Tengah.The research results find that the literacy culture program is important to be implemented from early childhood, starting in the family circle and continued to school age. School is an environment that has determining role in forming children’s reading interest. The programs implemented at PAUD Inklusi Saymara include “one day one story” program, in which the teacher will tell stories for the students via various media. The activity of book reading in compelling way will inspire children that reading is fun, and it will stimulate children’s reading interest. The second program is strengthening reading interest based on library. Library holds important role in fostering and developing awareness in reading. The third program is stimulating children’s skills in reading and writing through playful activities. The program to stimulate children’s reading and writing skills is according to the phases of reading and writing development on 4/6-year-old children. The last program is visiting bookstore to introduce and familiarize books for kids and build literacy culture from early childhood. Through the programs to strengthen literacy culture at PAUD Inklusi Saymara, it is proven that the children’s reading interest improves significantly.